The Stop Signal Task for Measuring Behavioral Inhibition in Mice With Increased Sensitivity and High-Throughput Operation - Caglayan, Alican; Stumpenhorst, Katharina; Winter, York (Frontiers in Behavioral Neuroscience, 2021)
Ceasing an ongoing motor response requires action cancellation. This is impaired in many pathologies such as attention deficit disorder and schizophrenia. Action cancellation is measured by the stop signal task that estimates how quickly a motor response can be stopped when it is already being executed. Apart from human studies, the stop signal task has been used to investigate neurobiological mechanisms of action cancellation overwhelmingly in rats and only rarely in mice, despite the need for a genetic model approach. Contributing factors to the limited number of mice studies may be the long and laborious training that is necessary and the requirement for a very loud (100 dB) stop signal. We overcame these limitations by employing a fully-automated home-cage-based setup. We connected a home-cage to the operant box via a gating mechanism, that allowed individual ID chipped mice to start sessions voluntarily. Furthermore, we added a negative reinforcement consisting of a mild air puff with escape option to the protocol. This specifically improved baseline inhibition to 94% (from 84% with the conventional approach). To measure baseline inhibition the stop is signalled immediately with trial onset thus measuring action restraint rather than action cancellation ability. A high baseline allowed us to measure action cancellation ability with higher sensitivity. Furthermore, our setup allowed us to reduce the intensity of the acoustic stop signal from 100 dB to 70 dB. We constructed inhibition curves from stop trials with daily adjusted delays to estimate stop signal reaction times (SSRTs). SSRTs (median 88 ms) were lower than reported previously, which we attribute to the observed high baseline inhibition. Our automated training protocol reduced training time by 20% while also promoting minimal experimenter involvement. This sensitive and labour efficient stop signal task procedure should therefore facilitate the investigation of action cancellation pathologies in genetic mouse models.